Age-dependent root canal instrumentation techniques: a comprehensive narrative review - Michael Solomonov; Hyeon-Cheol Kim; Avi Hadad; Dan Henry Levy; Joe Ben Itzhak; Oleg Levinson; Hadas Azizi (Restorative Dentistry & Endodontics)
The aim of this article was to review age-dependent clinical recommendations for appropriate root canal instrumentation techniques. A comprehensive narrative review of canal morphology, the structural characteristics of dentin, and endodontic outcomes at different ages was undertaken instead of a systematic review. An electronic literature search was carried out, including the Medline (Ovid), PubMed, and Web of Science databases. The searches used controlled vocabulary and free-text terms, as follows: ‘age-related root canal treatment,’ ‘age-related instrumentation,’ ‘age-related chemo-mechanical preparation,’ ‘age-related endodontic clinical recommendations,’ ‘root canal instrumentation at different ages,’ ‘geriatric root canal treatment,’ and ‘pediatric root canal treatment.’ Due to the lack of literature with practical age-based clinical recommendations for an appropriate root canal instrumentation technique, a narrative review was conducted to suggest a clinical algorithm for choosing the most appropriate instrumentation technique during root canal treatment. Based on the evidence found through the narrative review, an age-related clinical algorithm for choosing appropriate instrumentation during root canal treatment was proposed. Age affects the morphology of the root canal system and the structural characteristics of dentin. The clinician’s awareness of root canal morphology and dentin characteristics can influence the choice of instruments for root canal treatment.